(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research is good for certifying the impact of the text and its role in directing the light, and the light is concerned with the concept of the context, as the context helps in determining the appropriate word or structure in terms of what they desire on the tablet systems within the system system, and from here studying the meanings of words and phrases, and proving the indications that an analysis is required in That discourse and the situations in which it appears, each type has certain types of keys that emerge from the relationship of words and their locations in terms of structure, which contributes to revealing semantic shifts and highlighting the contextual Which is included in the term while embracing it with the other items of the text, so the contextual significance is resulting from the joining of the part with the whole, and the sentence with the text, and this distances the vocabulary from the lexical use that is outside the context in the light of the use, and then the research moves to clarifying the impact of the context in directing the meaning within the poetic text, The poetry of the poet Dick Al-Jin Al-Homsi was chosen in selected samples of his poetry, to show the diversity of his compositional styles, and the transmission of their connotations due to the influence of the context in which they were received.